Karakter Guru Ideal Dalam Buku Begini Seharusnya Menjadi Guru Karya Fu’ad Bin Abdul Aziz Asy-Syalhub - ., Zulkifli; ., Arnadi; ., Ubabuddin (TABYIN: JURNAL PENDIDIKAN ISLAM, 2021)
The ideal teacher character in this book should be a teacher by Fu'ad bin Abdul Aziz Asy-Syalhub. The teaching profession cannot be matched by any other profession in virtue and position, and (some) teaching professions are more noble and the more useful the science material being taught, the higher the dignity and degree of its owner. And the most noble knowledge is absolutely the science of syari'at, only then the other sciences, each according to its level. A teacher, if he gives up his deeds for Allah and intends his ta'lim to benefit humans, teach those who are good, and lift the ignorance of them, then that will be a plus for his goodness and a cause for additional rewards. The teacher's task is not only limited to delivering subject matter to students, it is even a tough and difficult task, but it will be easy for whom Allah Subhanahu wa ta'ala wants and makes easy. This task requires a teacher to be patient, trustworthy, sincere, and nurturing to those under him, namely his students.